Effect of temperature on growth performance of greater amberjack (SERIOLA DUMERILI Risso 1810) Juveniles. (23rd October 2017) - Fernández‐Montero, Alvaro; Caballero, Maria Jose; Torrecillas, Silvia; Tuset, Victor Manuel; Lombarte, Antoni; Ginés, Rafael Ruiz; Izquierdo, Marisol; Robaina, Lidia; Montero, Daniel
Abstract: In order to successfully diversify Mediterranean aquaculture, it is necessary to determine optimum culture conditions of potential candidate species such as greater amberjack ( Seriola dumerili ). Among culture conditions, rearing temperature is a key factor for achieving optimum growth and maintaining fish welfare. However, little is known about the optimum culture conditions of greater amberjack ( Seriola dumerili ). Thus, the aim of this study was to determine the effect of three different rearing temperatures (17, 22 and 26°C) during 120 days on growth performance, body morphometry, biochemical composition, gut transit and liver morphology of greater amberjack ( Seriola dumerili ) juveniles. After 120 days of rearing, fish raised at 26°C showed higher ( p  < .05) body weight and specific growth rate than fish held at lower temperatures, as well as improved feed utilization, protein efficiency and nutrient retention percentages. Fish stomach emptying was faster ( p  < .05) in fish raised at 26°C than in fish held at 22°C and 17°C. Similar results were obtained for gut transit time, being gut emptying faster ( p  < .05) in fish reared at 26°C than in fish cultured at lower temperatures. Rearing temperature also induced changes in fish morphology which resulted in a higher ( p  < .05) caudal propulsion efficiency index for fish reared at 26°C. Based on these results, we conclude that greater amberjack fingerlings perform better at 26°C than at 22°C or 17°C.